A novel laser-based method to measure the adsorption energy on carbonaceous surfaces. (March 2021) - Duca, D.; Pirim, C.; Vojkovic, M.; Carpentier, Y.; Faccinetto, A.; Ziskind, M.; Preda, C.; Focsa, C.
Abstract: The reactivity of carbonaceous surfaces bears a fundamental role in various fields, from atmospheric chemistry and catalysis to graphene and nanoparticles. This reactivity is mainly driven by the surface chemical composition and by the strength of the interaction between the adsorbates and the surface (physi-/chemisorption). While the surface composition of complex natural samples can be well characterized, adsorption energies (ergo, adsorption processes) of the corresponding adsorbate/adsorbent systems are often overlooked. We propose a novel laser-based method for measuring the adsorption energy of chemical species on various carbonaceous surfaces. The proof of concept of this original method has first been demonstrated by deriving adsorption energies of various systems consisting of polycyclic aromatic hydrocarbons and activated carbon. The great potential of this fast, spatially resolved, and surface-sensitive method, which can also act as a defect density probe at the mesoscale, has been further demonstrated through the study of systems of increasing complexity. Graphical abstract: Image 1